2019
DOI: 10.3389/fphys.2019.01201
|View full text |Cite|
|
Sign up to set email alerts
|

Physiological and Biochemical Effects of Intrinsically High and Low Exercise Capacities Through Multiomics Approaches

Abstract: Regular exercise prevents lipid abnormalities and conditions such as diabetes mellitus, hypertension, and obesity; it considerably benefits sedentary individuals. However, individuals exhibit highly variable responses to exercise, probably due to genetic variations. Animal models are typically used to investigate the relationship of intrinsic exercise capacity with physiological, pathological, psychological, behavioral, and metabolic disorders. In the present study, we investigated differential physiological a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 54 publications
(65 reference statements)
4
21
0
Order By: Relevance
“…Studies showed the potential role of Butyricicoccus in exercise physiology. For example, Tung et al found a greater abundance and diversity of GM in intrinsic high exercise capacity mice than in low exercise capacity mice, indicating the potential effect of GM and functional proteins on intrinsic exercise capacity [41]. The important role of nutrients in muscle strength and HGS has been revealed in previous study [42], which is consistent with our results.…”
Section: Discussionsupporting
confidence: 93%
“…Studies showed the potential role of Butyricicoccus in exercise physiology. For example, Tung et al found a greater abundance and diversity of GM in intrinsic high exercise capacity mice than in low exercise capacity mice, indicating the potential effect of GM and functional proteins on intrinsic exercise capacity [41]. The important role of nutrients in muscle strength and HGS has been revealed in previous study [42], which is consistent with our results.…”
Section: Discussionsupporting
confidence: 93%
“…These data corroborate previous results obtained by other authors comparing obese children with sedentary and active lifestyles 57 . Moreover, several studies have demonstrated a possible role for gut microbiota in the maintenance of muscle strength, as well as in the adaptation of physiological functions and exercise capacity 58 , 59 . These findings could justify the possible connection between our changes in gut microbiota composition and functionality and the beneficial effects of exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Then, operational taxonomic units (OTUs) with similarity greater than 97% were clustered and a species classification analysis performed. The sequences were further analyzed using a Ribosomal Database Project Naive Bayesian rRNA Classifier (version 2.5) to categorize the microbiota and investigate the relative proportions of microbiota existing in an indicated sample [ 19 ].…”
Section: Methodsmentioning
confidence: 99%